Bacterial glycerol oxidation coupled to sulfate reduction at neutral and acidic pH - Santos, Sidnei C. (2018)
Glycerol is a main co-product of biodiesel production. Crude glycerol may serve as a cheap and attractive substrate in biotechnological applications, e.g. for the production of valuable chemicals or as an electron donor for reduction processes. In this work, sulfate reduction with glycerol was studied at neutral and acidic pH using bioreactor sludge samples and Tinto River sediments as a source of inoculum, respectively. Communities of sulfate-reducing bacteria (SRB) and fermentative bacteria were co-enriched at both pH values. Molecular analyses revealed that sequences belonging to Desulfomicrobium genus were dominant in the cultures enriched at pH 7, while Desulfosporosinus sequences dominated in the culture enriched at pH 4. Glycerol conversion was coupled to sulfate reduction, but the substrate was incompletely oxidized to acetate in the neutrophilic enrichments, and acetate, lactate, and 1,3-propanediol under low pH conditions. Two strains belonging to Desulfomicrobium and Proteiniphilum genera were isolated from the neutrophilic enrichments, but the first isolate was not able to use glycerol, which suggests a syntrophic relationship between glycerol-degrading fermentative bacteria and SRB. A Clostridium strain able to grow with glycerol was isolated from the low pH enrichment. Our data indicate that glycerol promotes the growth of sulfate-reducing communities to form sulfide, which can be used to precipitate and recover heavy metals.